2008
DOI: 10.4315/0362-028x-71.11.2217
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Salmonella Serotypes Isolated from Cantaloupe and Chile Pepper Production Systems in Mexico by PCR–Restriction Fragment Length Polymorphism

Abstract: A study was conducted in 2006 to determine the prevalence of Salmonella on three cantaloupe farms in Matamoros, Coahuila, Mexico, and on one farm that cultivates chile peppers var. Bell in Culiacán, Sinaloa, Mexico. Samples from cantaloupe farms consisted of cantaloupe rinses, irrigation water, water from furrows in the field, and workers' hands. Samples from the chile pepper farm consisted of rinses of chile peppers obtained at the field, pepper rinses obtained at the packing house, and irrigation water from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 18 publications
0
26
0
4
Order By: Relevance
“…Obtained restriction DNA fragments are separated on agarose gel and the band profiles are compared. Although the RFLP system is easy to perform, inexpensive and rapid [9,10], the analysis using single gene and enzyme usually provides limited discriminatory power [11]. PFGE is an efficient sub-typing method and commonly used in outbreak investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Obtained restriction DNA fragments are separated on agarose gel and the band profiles are compared. Although the RFLP system is easy to perform, inexpensive and rapid [9,10], the analysis using single gene and enzyme usually provides limited discriminatory power [11]. PFGE is an efficient sub-typing method and commonly used in outbreak investigations.…”
Section: Introductionmentioning
confidence: 99%
“…The PCR analyses of the virulence genesdemonstrated suitable targetgene for discriminating among Salmonellaserotypes. Studies have also shown that this method is rapid and reproducible in identification ofisolates [19]. Theseresults showed that these methods can potentially beapplied for identification of Salmonella typhimurium Various primers sets targeting Salmonella16SrRNA, sitC and fliC genes have been designed for research purposes [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of these human pathogens was also reported on fruits and vegetables (including tomatoes and peppers) in the market place (Arthur et al, 2007;Benjamin et al, 2013;Gallegos-Robles et al, 2008;Greene et al, 2008;Guchi and Ashenafi, 2010;Micallef et al, 2012;Weber et al, 2006;Butterfield, 1997, 1999). Even though human pathogens are fairly uncommon in the crop production environment, fresh produce has been implicated in at least 130 outbreaks of gastroenteritis in the U.S. since 1996.…”
Section: Introductionmentioning
confidence: 91%